COMPUTATIONAL FLUID DYNAMICS (CFD) APPLICATION FOR VENTILATION STUDIES IN BROILER HOUSES - Curi, Thayla M. R. de C.; Moura, Daniella J. de; Massari, Juliana M.; Mesquita, Marcio; Pereira, Danilo F. [UNESP] (Soc Brasil Engenharia Agricola, 2017)
With the recent increase in the number of acclimatized broiler houses in Brazil, design and adaptation of facilities to withstand the tropical weather conditions enabling the maintenance of ideal conditions without increasing costs have been major challenges. The aim of this study was to evaluate the ventilation system in solid -wall broiler houses using computational fluid dynamics (CFD). The research was carried out in the city of Amparo - SP (Brazil). The facility consisted of a broiler house enclosed by masonry sidewalls with tunnel ventilation equipped with exhaust fans (air outlet) and cooling pads (air inlet). The following variables were collected: wind speed and dry bulb temperature over 27 equidistant points inside the house at bird height (0.30 m above the floor), wind speed in inlet cooling pad, and static pressure in the outlet (exhaust fans) as a boundary condition. The data were monitored at the most critical time of the day 2 pm during the final rearing stage in summer. The CFD technique allowed visualizing the air flow according to each running condition for exhaust fans, as well as determined the best setting of exhaust fans, avoiding a low air area renewal and turbulence.
Keywords: Broiler house; computational modeling; environmental control; poultry; thermal comfort